Elements of Sanghahawatthu 4 - Phannadhepo, Phra Bunthun (Journal of Dhamma for Life, 2021)
This academic paper aims to present the elements of the Sankhahavathu 4 by studying and describing them through elemental analysis. The study found that alms or giving is generosity, sacrifice, sharing both objects and teachings. There are 3 types of alms: with power from intention renunciation, abstinence, and with alms giving. There are 10 things to eat, according to Buddhism, namely: rice, water, cloth, vehicles, flowers, perfumes, caresses, beds, shelters, and lamps. The principle of almsgiving consists of six elements, namely, the one who gives 3 and the one who receives 3. There are 21 types of virtue of giving. There are 5 virtues of Piyawaca: Speak at the right time, speak only the truth, Speak sweetly. Speak with benefits and speak with compassion. Attha-cariya is the conduct of benefit according to the Buddha-cariya. There are 3 elements: Lokattha-cariya, Nya-tattha-cariya, and Buddha-cariya. Samanattata is self-equality according to the meaning of the commentary, which is to present oneself in society with equality with others, being compatible with others, being consistent.